Management of Nanostim leadless pacemaker early-life battery failures. A single center experience. (24th May 2021) - Oosterwerff, F; Salavati, A; Adiyaman, A; Ghani, A; Smit, JJJ; Ramdat Misier, A; Delnoy, PPHM; Elvan, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/introduction Early studies of the Nanostim leadless pacemaker demonstrated technical feasibility effective pacing performance at the short-term. However, recently the Nanostim proved to be susceptible to early-life battery failures. Purpose In this study, we addressed the following research questions: 1) What percentage of Nanostim LPs experience early-life battery failure? 2) Is Nanostim extraction and subsequent pacemaker reimplantation safe and effective? 3) Is three monthly follow-up under the Nanostim advisory effective at preventing Nanostim LP related in-between hospitalizations? Methods In a retrospective study, we collected data of 49 Nanostim implanted patients with a mean follow up of 3 (±1.5) years at our tertiary hospital. Results Nanostim early-life battery failure in our population was 37% (18/49). Extraction of 14 Nanostim pacemakers (device age 1040  ± 467 days) in an older population (80 ± 7 years) was safe (0 complications) and effective (80% extraction success, 100% reimplantation success). All known cases of early-life battery failure were identified during the three monthly follow-up consultations. Conclusions Nanostim LP early-life battery failure is substantially higher than previously reported. In case of dysfunction Nanostim extraction in an older population is safe and effective. Three monthly follow-up is effective at preventing in-between Nanostim related hospitalization.